Characterization of Patients with Biopsy-Proven Non-Alcoholic Fatty Liver Disease and Normal Aminotransferase Levels - YILMAZ, YUSUF (MEDICAL UNIV PRESS, 2019)
Background & Aims: Non-alcoholic fatty liver disease (NAFLD) is one of the major causes of abnormal liver function tests in hepatology practice. However, not all patients with NAFLD have increased aminotransferase levels. The aim of this study was to compare the clinical and histologic characteristics of patients with biopsyproven NAFLD showing normal versus elevated aminotransferase levels. Methods: We retrospectively reviewed 515 patients with biopsy-proven NAFLD. Patients with ALT <= 40 U/L and AST <= 37 U/L were considered as having normal liver enzymes. A histological fibrosis score F >= 3 was used to define advanced fibrosis. Results: Of the 515 study participants, 107 (20.8%) had normal liver enzymes. Compared with patients showing elevated liver enzymes, those with normal aminotransferase levels were older and most commonly University, women. Moreover, they had a higher body mass index and more frequently showed metabolic risk factors metabolic syndrome, diabetes mellitus, hypertension, higher waist and hip circumferences). Although liver histology tended to be less severe in patients with normal liver enzymes, the prevalence of advanced fibrosis was similar in the two groups. Diabetes mellitus (odds ratio [OR] = 2.12, 95% confidence interval [CI] = 1.46-3.91, p < 0.001) and age (OR = 1.14, 95% CI = 1.07-1.24, p < 0.05) were identified as independent predictors of advanced fibrosis in patients with normal aminotransferase levels. Conclusions: NAFLD with normal aminotransferase levels is characterized by a severe metabolic profile and a prevalence of advanced fibrosis similar to that identified in cases with elevated aminotransferase levels.
Keywords: non-alcoholic fatty liver disease; liver enzymes; aminotransferases; biopsy; advanced fibrosis; FIBROSIS STAGE